Place-based learning in social studies education: a systematic review of implementation, outcomes, and enabling conditions - Salvetri Salvetri; Jeki Haryanto (Global Econedu, 2026)
Requests that schools become more relevant, more civically involved, and more rooted in local areas have generated a fresh intellectual interest in place-based learning. Although social studies education seems to be one of the area’s most suitable to this kind of approach, it is rather unclear to what extent it actually happens. The paper presents a systematic literature review of studies reporting on the use of place-based learning in social studies education together with the outcomes and the enabling circumstances that were identified. After following the recommendations of the PRISMA 2020 statement and scanning the Scopus database in a structured way, 255 studies, including duplicates, were found. The records were then deduplicated, and titles, abstracts, and full papers were scrutinized to identify those matching the eligibility criteria. Eighteen research and conceptual papers published between 2021 and 2026 were finally selected, and a thematic synthesis was used to obtain themes that can be generalized. Results show that place-based learning is mainly conducted using community-based collaborations, local-heritage and archival investigations, and field-based geographic investigations. It is also consistently linked to gains in civic responsibility, conceptual grasp, and emotional involvement, and at the same time it helps teacher training. A different understanding of place from that of most mainstream theories came out as a unique theoretical thread: Indigenous and decolonial ideas of place. The study also highlights areas where research could be made more methodologically sound and equitable. A number of educational topics, such as curriculum development, teacher education, and policy, are also discussed, and a list of possible research topics related to longitudinal, comparative, and outcome-based research is suggested.